Plyometric Training in Normobaric Hypoxia improves Jump Performance - Coşkun, Betül; Aras, Dicle; Akalan, Cengiz; Kocak, Settar; Hamlin, Michael J. (International Journal of Sports Medicine, 2021)
Strength training in hypoxia has been shown to enhance hypertrophy and function of skeletal muscle, however, the effects of plyometric training in hypoxia is relatively unknown. Therefore, this study aimed to examine the effects of plyometric training in hypoxia compared to normoxia on body composition, sprint and jump parameters. Twenty-three male physical education students (20.4±2.0 years, mean±SD) participated in the study and were divided into a plyometric training in hypoxia (PTH, n=8), plyometric training in normoxia (PTN, n=7) or control group (C, n=8). The PTH group trained in normobaric hypoxia (approximately 3536 m) 3 days/week for 8 weeks, while the PTN trained in normoxia. PTH induced significant improvements from baseline to post-testing in countermovement-jump (37.8±6.7 cm, 43.4±5.0 cm, p<0.05), squat-jump (35.4±6.2 cm, 41.1±5.7 cm, p<0.05), drop-jump height (32.8±6 cm, 38.1±6 cm, p<0.05) and 20-m sprint performance (3257.1±109.5 ms, 3145.8±83.6 ms, p<0.05); whereas PTN produced significant improvement only in countermovement-jump (37.3±4.8 cm, 40.5±4.5 cm, p<0.05) and 20-m sprint performance (3209.3±76.1 ms, 3126.6±100.4 ms, p<0.05). Plyometric training under hypoxic conditions induces greater improvement in some jump measures (drop-jump and squat-jump) compared to similar training in normoxia.
Keywords: plyometrics; simulated hypoxia; live low-train high; explosive power